Meconium-stained amniotic fluid viscosity and chest x-ray findings - Ricki Rajagukguk; Muhammad Sholeh Kosim; Arsita Eka Rini; Mardiana Mardiana (Paediatrica Indonesiana, 2012)
Background Approximately 8-15% of all infants are born withevidence of meconium-stained amniotic fluid (MSAF). Manyof these infants rapidly initiate a good respiratory response andare othenvise vigorous. Other infants present v.ith a variety ofrespiratory distress. Chest x-ray imaging is the main test done toevaluate respiratory distress in order to differentiate pulmonaryand extrapulmonary etiologies.Objective To determine the relationship between viscosity ofMSAF and chest x-ray imaging results.Methods This cross-sectional study was held from January to June2011, as a continuation of a previous study from August 2009 toMay 2010 at Kariadi Hospital, Semarang, Indonesia. Data wastaken from medical records of babies who were born v.ith MSAF.MSAF viscosity measurements by the investigator and laboratorytechnician were assessed by Kappa test in the previous study witha result of 0.7 4. X-ray findings were determined by the radiologiston duty at that time. Chi square and logistic regressiontests wereused for statistical analysis.Results There were 48 subjects consisting of 26 males and 22females. Chest x-ray imaging results showed normal findings in33.3% of subjects, pneumonia in 58.3% of subjects and meconiumaspiration syndrome in 8.3% of subjects. Thick viscosity MSAFwas significantly correlated to abnormal x-ray imaging (RR= 2.046;P=0.004; 95%CI 1.12 t03.72).Conclusion Thick MSAF viscosity significantly increased therisk of abnormal chest x-ray findings. [Paediatr Indones.2012;52:336-40].